BARIUM AND CALCIUM NIOBATE CERAMICS: SPECIFIC FEATURES OF THEIR STRUCTURE - O.S. Guseva (Tver State University, 2021)
We obtained and studied the samples of ceramics based on barium niobate and calcium niobate CaxBa1-xNb2O6 with different percentages of barium and calcium (x=1; 0,9; 0,8; 0,7; 0,6; 0,5; 0,4; 0,3; 0,2; 0,1 and 0). The effect of the sintering temperature on the structure and dielectric properties of ceramics has been investigated. One batch of the samples was sintered at a temperature of 1100°C, the second at 1250°C. We have shown that the sintering temperature of 1100°C is not enough to obtain good ferroelectric properties, and the process of grain recrystallization is not completed. According to studies of the elemental composition, in samples sintered at a temperature of 1250°C with the Ca content greater than 0,5, Ba atoms are not present in all grains, which also affects the course of the temperature dependences of the dielectric constant A sample with x=0,3 is distinguished by its dielectric properties.